Parallel Burnup Analysis of Long-life Fast Reactors Using Multi-core Programming - Imam Taufiq; Zaki Su'ud; Abdul Waris; Mitra Djamal (Institut Teknologi Bandung, 2010)
A scalable parallel program for burnup analysis of long-life fast reactor has been succesfully built. The scalability test was conducted by comparing the program performance on dual-core and quad-core platforms. The best speedup gain were 1.72 on dual core 2.0 GHz, 3.58 on quad-core 2.4 GHz and 3.05 on quad-core 3.2 GHz. The slight drop of the speedup on quad-core 3.2 GHz could be well explained in connection with communication-time needed in running parallel version of the program.